The Risk of COVID-19 Pandemic in Patients with Moderate to Severe Plaque Psoriasis Receiving Systemic Treatments - Paolo Gisondi; Francesco Bellinato; Andrea Chiricozzi; Giampiero Girolomoni (Vaccines, 2020)
Chronic plaque psoriasis is an inflammatory skin disease affecting 2–3% of the general population. Approximately one-third of patients are candidates for systemic immunosuppressive treatments, such as synthetic or biological disease-modifying antirheumatic drugs, because of disease extensions, localization in sensitive or visible areas and/or resistance to topical treatments. These therapies have been associated with increased risk of infection, including upper respiratory tract viral infection. Psoriasis is frequently associated with cardio-metabolic comorbidities, such as obesity and diabetes, that are risk factors for poor prognosis in the case of coronavirus disease (COVID-19) pneumonia. A narrative review of the literature based on an electronic search of the PubMed® database was undertaken with the objective of investigating whether there is an increased risk of COVID-19 infection in psoriasis patients on systemic treatment. Original articles, such as case reports, published up to 1 November 2020 were included. There is no evidence that patients with moderate-to-severe psoriasis receiving systemic treatments, including biologics, have higher risk of SARS-CoV-2 infection and/or increased hospitalization and death related to COVID-19 compared to the general population. Several case reports described full recovery from COVID-19 with favorable outcomes in psoriasis patients who were being treated with synthetics or biologicals. Nonetheless, caution should be maintained in this setting, and more data are needed to draw definitive conclusions.